Electrode assembly structure for all-solid battery and its manufacturing method
Patent Information
- Application Number
- KR1020240128983
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2026-09-11
- Estimated Expiration
- 2044-09-24
Smart Images

Figure 112024104093018-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present disclosure relates to an all-solid-state battery, and specifically, to an electrode assembly structure having high energy density and high mechanical strength, a material constituting the electrode, and a method for manufacturing the same. Background Technology
[0002] Unless otherwise indicated in this specification, the contents described in this section are not prior art for the claims of this application, and are not to be recognized as prior art simply because they are included in this section.
[0003] Secondary batteries are rechargeable batteries. They are batteries that can be recharged and used multiple times even after being discharged once, and are also called rechargeable batteries. In contrast, primary batteries are batteries that cannot be recharged after being used once.
[0004] There are various types of rechargeable batteries, among which lithium-ion batteries are the most widely used. Lithium-ion batteries are used in a wide range of electronic devices, including smartphones, laptops, and electric vehicles. Other representative examples of rechargeable batteries include nickel-hydrogen batteries (NiMH) and lead-acid batteries.
[0005] Rechargeable batteries fundamentally have a basic structure consisting of a positive electrode, a negative electrode, and an electrolyte located between them. All-solid-state batteries utilize a solid material instead of a liquid for the electrolyte, thereby reducing fire hazards and improving energy density. The process of forming a chip containing information and its surrounding structure during semiconductor manufacturing is called the "semiconductor packaging process." Figure 1 illustrates the Fan-In structure and the Fan-Out structure, which are two major processes in semiconductor packaging. Among wafer-level packages in semiconductor packaging technology, both Fan-In and Fan-Out structures exist. The Fan-In structure is a package in which wiring and an insulating layer for packaging are formed directly on the wafer. This structure has the advantage of high electrical characteristics because electrical conductors are assembled directly on the chip without additional media such as a substrate, and it enables a low-cost process when the number of chips on a wafer is large. Compared to the conventional Fan-In structure, the Fan-Out structure is a technology that improves semiconductor durability and productivity by reducing the chip area while installing a protective structure called EMC around it.
[0006] However, the Fan-In structure has the disadvantage that the physical and chemical protection of the package is weak because the silicon chip is packaged directly. The Fan-Out structure has emerged as a package that can overcome the disadvantages while retaining the advantages of the Fan-In structure. The Fan-Out structure has the advantage of improving the physical and chemical stability of the package itself, along with effects such as convenience in package testing and improved yield rates.
[0007] Rechargeable batteries are rechargeable batteries used in various fields, such as electric vehicles (EVs) and energy storage systems (ESS), and their scope of application is recently expanding to personal mobility devices (PMs) and drones. However, currently used rechargeable batteries face limitations in energy density and mechanical strength, requiring improvements in performance and safety. Although next-generation rechargeable batteries currently under research possess high performance, they face difficulties in commercialization due to certain drawbacks and high costs. To address these issues, we propose an electrode assembly structure utilizing a high-energy-density adhesive material and heterogeneous technology—specifically, an electrode assembly structure based on the Fan-Out structure of semiconductor packaging and a support structure using a polymer film material.
[0008] The modern rechargeable battery industry is utilized in various application fields, but it faces several major challenges. First, currently used rechargeable batteries have limitations in energy density, necessitating technologies that provide higher energy densities. This is particularly critical in high-performance applications such as electric vehicles (EVs). Additionally, enhancing the structural stability of batteries is a critical task. Batteries must possess high mechanical strength and stability to prevent damage from shocks or physical stress and to extend their lifespan. Furthermore, it is necessary to lower production costs while maintaining high performance. This serves as an essential factor for the popularization and commercial success of next-generation rechargeable batteries. Finally, current liquid electrolyte-based batteries pose risks of fire and explosion, necessitating research into next-generation batteries with safer electrolytes and materials to address these issues. Prior art literature
[0009] 1. Korean Patent Publication No. 10-2021-0033722 (March 29, 2021) 2. Korean Patent Publication No. 10-2021-0108566 (September 3, 2021) The problem to be solved
[0010] The electrode assembly for a next-generation secondary battery and the method for manufacturing the same according to the embodiment improve energy density and mechanical strength by applying a Fan-Out structure derived from semiconductor packaging technology to the electrode assembly structure. The Fan-Out structure is a structure that improves electrical conductivity and mechanical strength by forming wiring directly on a wafer. By applying this to the electrode assembly of a battery, the performance of the battery can be maximized. Second, a conductive material (the insulating part of the Fan-Out structure) is added to the solid electrolyte to correct the electrical conductivity and energy density of the electrode and prevent delamination that may occur due to volume changes. Third, an Interpenetrating Polymer Network (IPN) structure combining polyphenylene sulfide (PPS) and polyarylate (PAR) polymers is used to increase the mechanical strength and chemical stability of the battery, and PTFE is used as a cathode binder to enhance electrical conductivity and chemical stability. By providing an insulating structure that allows current to flow through the insulating structure, the problem of electrical conductivity can be resolved.
[0011] In addition, the embodiment provides a structure in which one of two fan-out structures, from which the lower structure of the EMC has been removed in a fan-out structure, is inverted and combined vertically.
[0012] In addition, in the embodiment, the wiring on both sides is combined to form a single electrode, and the structure is replaced with an upper and lower positive and negative plate. The existing insulator is replaced with a conductive structure to facilitate electrical conduction. Furthermore, the EMCs on both sides of the electrolyte are replaced with a support structure that can improve the mechanical strength of the battery while reducing the width of the electrolyte.
[0013] In addition, the embodiments propose an electrode assembly structure, a substrate connection method, and suitable materials that can be used in next-generation secondary batteries, based on promising industrial fields analyzed in quantitative and qualitative analyses.
[0014] However, the problem to be solved according to one embodiment is not limited to that mentioned above. means of solving the problem
[0015] The connecting material and electrode assembly structure for fabricating a next-generation secondary battery according to the embodiment may include: an adhesive material such as a binder used in the process of combining a polymer film support layer and a conductive layer; an electrode assembly structure formed by including support structures on both sides of a solid electrolyte and covering the top and bottom with a positive plate and a negative plate; a solid electrolyte located between the positive and negative electrodes; and a conductive structure mounted between the electrode plate and the electrolyte in the assembly structure.
[0016] In addition, the electrode assembly can be combined vertically with two models based on a model in which the bottom part of the protective layer is partially reduced in a fan-out structure, so that only the side support structures of the solid electrolyte exist.
[0017] In addition, the electrode, which is the electrode plate of the electrode assembly having the above-mentioned fan-out structure, is configured in a form where two wires of the fan-out structure are combined into one, and the upper and lower combined models can form the positive plate and the negative plate, respectively.
[0018] In addition, the support structure may have a width corresponding to the difference in width between the upper and lower electrode plates and the solid electrolyte.
[0019] In addition, the support structures on both sides of the solid electrolyte may include a polymer film formed by combining polyphenylene sulfide (PPS) and polyarylate (PAR) polymers into an interpenetrating network structure (IPN).
[0020] In addition, polymer films with an IPN structure can be heat-treated at a temperature of about 300°C to 350°C to improve mechanical strength and chemical stability.
[0021] In addition, the electrode assembly structure may include a conductive structure located between the electrolyte and the anode plate to improve electrical conductivity and energy density.
[0022] In addition, the conductive structure can be spaced apart above and below the solid electrolyte.
[0023] In addition, the conductive structure may include a conductive film layer or fiber to improve electrical conductivity and energy density.
[0024] Additionally, the conductive structure may comprise a conductive film layer or fiber containing at least one of copper, nickel, aluminum, and silver, a metallic material in the form of a metal fiber or foil; a carbon-based material comprising any one of graphite, carbon black, carbon fiber, carbon nanofiber, and carbon nanotube; a conductive polymer of a polyphenylene derivative or a polyaniline derivative; and may include a mixture of the metallic material, the carbon-based material and the conductive polymer.
[0025] In addition, polytetrafluoroethylene (PTFE) may be used as the adhesive material to connect the anode film and the conductive layer. The adhesive material can serve as a binder interposed between the anode layer and the conductive layer to mechanically bond them. Here, the anode layer refers to a layer containing an anode current collector and an anode active material, and the conductive layer may include a conductive film layer or fiber disposed between the anode layer and a solid electrolyte to assist in electron transfer. The adhesive material can improve the interfacial adhesion between the anode layer and the conductive layer, thereby improving the mechanical stability and electrical connectivity of the electrode structure.
[0026] In addition, the solid electrolyte may be a solid electrolyte composed of a sulfide-based material.
[0027] In addition, the solid electrolyte made of a sulfide-based material has an argyrodite-type crystal structure and includes a compound represented by the following chemical formula Li6PS5X, wherein X is one or more elements selected from Group 17 of the periodic table, and the elements may include at least one of Cl, Br, and I. Effects of the invention
[0028] The electrode assembly for a next-generation secondary battery and the method for manufacturing the same as described above
[0029] The decrease in electrical conductivity and energy density caused by delamination between the NCM and the solid electrolyte during the conventional charge / discharge process can be compensated for, and structural stability and physicochemical resistance of the battery can be improved by utilizing support structures on both sides compared to conventional electrodes. The support structures are made of materials with strong fire resistance and self-extinguishing properties, incorporating the advantages of fire-resistant solid electrolytes, and the electrode structure using a smaller amount of solid electrolyte than conventional solid electrolytes can resolve the cost issue that is a problem of conventional all-solid-state batteries.
[0030] In addition, through the embodiments, the electrical connection between the conductive material and the active material within the electrode can be strengthened to facilitate the movement of electrons. This allows for a reduction in the internal resistance of the electrode and an increase in the power density of the battery.
[0031] In addition, as shown in the examples, the bonding strength is superior compared to the commonly used PVDF, thereby increasing the structural stability of the electrode and preventing performance degradation caused by the detachment of the active material or volume changes during cycling.
[0032] In addition, the uniformity of the electrode is maintained through the examples, ensuring even distribution and adhesion of the active material. This improves the overall performance of the electrode and can maximize energy density.
[0033] In addition, through the examples, manufacturing in a dry process is possible as an alternative to the commonly used wet process, thereby reducing the time and cost consumed compared to the existing process and enabling superior price competitiveness in the manufacturing process of the battery itself.
[0034] The effects of the present invention are not limited to the effects described above, and should be understood to include all effects that can be inferred from the configuration of the invention described in the detailed description of the invention or the claims. Brief explanation of the drawing
[0035] Figure 1 is a diagram showing the Fan-In structure and the Fan-Out structure, which are two major processes in the semiconductor packaging process. FIG. 2 is a schematic cross-sectional view including wiring (100) through which electricity flows, an insulator (110) connecting the chip and the wiring, a chip (120), and an EMC (130) protecting the chip in a Fan-Out structure corresponding to the basic structure of an all-solid-state secondary battery structure according to an embodiment. FIG. 3 is a schematic cross-sectional view in which two structures are combined in an inverted state, wherein the lower EMC (130) structure is reduced in size and the EMC (130) is located only at both ends of the chip (120) in a Fan-Out structure corresponding to the basic structure of an all-solid-state secondary battery according to one embodiment of the present invention. FIGS. 4A, 4B, and 4C are drawings showing an electrode structure according to an embodiment viewed from above, excluding the anode plate. FIG. 5 is a drawing of a film for a conductive structure that can be disclosed in the form of a film and a fiber in an embodiment. FIGS. 6 and 7 are drawings illustrating application examples of a fan-out structure according to an embodiment. Figure 8 is a diagram showing an IPN structure and a semi-IPN structure. Figure 9 is a diagram comparing the performance of PTFE and PVDF. Specific details for implementing the invention
[0036] Hereinafter, embodiments disclosed in this specification will be described in detail with reference to the attached drawings. Identical or similar components regardless of drawing symbols are assigned the same reference number, and redundant descriptions thereof will be omitted. The suffixes "module" and "part" used for components in the following description are assigned or used interchangeably solely for the ease of drafting the specification and do not inherently possess distinct meanings or roles. Furthermore, in describing embodiments disclosed in this specification, if it is determined that a detailed description of related prior art could obscure the essence of the embodiments disclosed in this specification, such detailed description will be omitted. Additionally, the attached drawings are intended only to facilitate understanding of the embodiments disclosed in this specification; the technical concept disclosed in this specification is not limited by the attached drawings, and it should be understood that they include all modifications, equivalents, and substitutions that fall within the spirit and technical scope of the present invention.
[0037] Terms including ordinal numbers, such as first, second, etc., may be used to describe various components, but said components are not limited by said terms. These terms are used solely for the purpose of distinguishing one component from another.
[0038] When it is stated that one component is "connected" or "connected" to another component, it should be understood that while it may be directly connected or connected to that other component, there may also be other components in between. On the other hand, when it is stated that one component is "directly connected" or "directly connected" to another component, it should be understood that there are no other components in between.
[0039] In this application, terms such as “comprising” or “having” are intended to specify the existence of the features, numbers, steps, actions, components, parts, or combinations thereof described in the specification, and should be understood as not precluding the existence or addition of one or more other features, numbers, steps, actions, components, parts, or combinations thereof.
[0040] In this specification, the term "part" includes a unit realized by hardware, a unit realized by software, and a unit realized using both. Additionally, one unit may be realized using two or more hardware, and two or more units may be realized by one hardware.
[0041] Some of the operations or functions described herein as being performed by a terminal, device, or device may instead be performed by a server connected to said terminal, device, or device. Likewise, some of the operations or functions described as being performed by a server may also be performed by a terminal, device, or device connected to said server.
[0042] Hereinafter, the present invention will be described in detail with reference to the attached drawings.
[0043] Generally, the electrode assembly structure of all-solid-state secondary batteries has utilized a configuration in which a positive electrode, consisting of a positive current collector and a positive active material bonded via a positive binder, a negative electrode, consisting of a negative current collector and a negative active material bonded via a negative binder, and a solid electrolyte located between them. However, when the electrode material and solid electrolyte are combined in this structure, the battery exhibits a characteristic of volume change during the charge-discharge process and the exchange of ions. For example, NCM shows a volume change of 3.4%, while silicon (Si) shows 400%, which causes a problem of excessive delamination at the interface between the electrode material and the solid electrolyte. This leads to a decrease in the ion conductivity and energy density of the all-solid-state battery. Furthermore, regarding sulfide-based solid electrolytes, which are the subject of much research due to their advantages over oxide and polymer-based electrolytes, it has been commonly cited as a problem that their mass production potential is extremely low due to the high cost of Li2S, the main raw material, and expensive processing costs.
[0044] In the embodiments, a novel structure of an all-solid-state secondary battery is proposed based on these points. An all-solid-state secondary battery according to one embodiment comprises: a positive electrode layer; a negative electrode layer; and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer; wherein the positive electrode layer comprises a state in which a positive electrode collector and a positive electrode active material are combined, and the negative electrode layer comprises a state in which a negative electrode collector and a negative electrode active material are combined, and wherein the battery comprises a conductive structure disposed between the positive electrode layer and the solid electrolyte, and between the negative electrode layer and the solid electrolyte.
[0045] The conductive structure is characterized by being spaced apart above and below the solid electrolyte and includes support structures disposed at both ends of the solid electrolyte, wherein the constituent material of the support structures is characterized by polyphenylene sulfide (PPS) and polyarylate (PAR) forming an interpenetrating network (IPN) structure, and wherein the anode layer and the cathode layer include the width of the solid electrolyte and the support structures on both sides.
[0046] FIG. 2 is a cross-sectional schematic diagram including a wiring (100) through which electricity flows, an insulator (110) connecting the chip and the wiring, a chip (120), and an EMC (130) protecting the chip in a Fan-Out structure corresponding to the basic structure of a solid-state secondary battery structure according to an embodiment.
[0047] Referring to Fig. 2, the Fan-Out structure of Fig. 2, which complements the disadvantages of the Fan-In structure characterized by having a chip attached that corresponds to the combined size of the chip (120) and EMC (130) of Fig. 2, has the advantage of improved physical / chemical protection functions due to the EMC (130) and low-cost processing compared to the Fan-In structure.
[0048] FIG. 3 is a schematic cross-sectional view of a Fan-Out structure corresponding to the basic structure of an all-solid-state secondary battery according to one embodiment of the present invention, in which the lower EMC (130) structure is reduced and the EMC (130) is located only at both ends of the chip (120), and the two structures are combined in an inverted state.
[0049] Referring to FIG. 3, the electrode assembly structure of the present invention has a structure in which two upper wires (100) are structurally combined and replaced with a positive plate, two lower wires (100) are structurally combined and replaced with a negative plate, two chips (120) and two insulators (110) coupled to each chip (120) are structurally combined and the chips (120) are structurally replaced with a solid electrolyte and the insulators (110) are structurally replaced with a conductive structure, and EMCs (130) coupled to both ends of the chips (120) are structurally combined and replaced with a support structure. In Figure 2, the existing Fan-Out structure is a structure used in semiconductor packaging processes, and has a structure in which the direction of current is formed left and right and two wires (100) are spaced apart on both sides. However, the electrode assembly structure of the present invention is characterized in that the upper two wires (100) are combined into one wire and the lower two wires (100) are combined into one wire, as the ions move up and down and undergo a charging and discharging process.
[0050] FIGS. 4a, 4b, and 4c are drawings showing an electrode structure according to an embodiment, viewed from above with the positive plate excluded. FIG. 4 shows an electrode assembly structure of the present invention substituted from FIG. 3, comprising a positive plate (300) and a negative plate (310), a solid electrolyte (340) located between the positive plate and the negative plate, a support structure (320) located at both ends of the solid electrolyte (340), and a conductive structure (330) spaced apart at the top and bottom of the solid electrolyte (340). It is characterized by using polytetrafluoroethylene (PTFE) as a positive binder material that combines the positive active material of the positive plate (300) and the positive current collector of FIG. 3. This can reinforce the electrical conductivity and chemical stability of the battery and enables the use of a dry process compared to the conventional PVdF material used as a positive binder, which is used in a wet process. The solid electrolyte (340) located between the positive plate (300) and the negative plate (310) of Figure 4 is characterized by including a sulfide-based solid electrolyte. The support structure (320) located at both ends of the solid electrolyte (340) of Figure 4 is characterized by having a width corresponding to the difference in width between the upper and lower plates and the solid electrolyte, and the material of the support structure (320) is characterized by polyphenylene sulfide (PPS) and polyarylate (PAR) being combined in an interpenetrating network (IPN) structure. The interpenetrating network (IPN) structure refers to a cross-linked structure formed by the interpenetration of two or more polymer networks.The process of manufacturing the above interpenetrating network (IPN) structure includes: a process of preparing a uniform solution by dissolving high-purity PAR powder and high-purity PPS powder in respective solvents (organic solvents containing NMP or DMF); a process of forming a uniform mixed solution by adding a crosslinking agent and an initiator to the two solutions; and a process of forming an IPN structure by preparing the solution thus formed into a film and then undergoing a process such as heat treatment or light irradiation at an appropriate temperature (about 300°C to 350°C).
[0051] The support structure (320) of the above interpenetrating network (IPN) structure has a cost advantage by reducing the amount of high-priced solid electrolyte required, which is a problem in the past, and at the same time, the physical, chemical, and mechanical stability of the battery can be secured similarly to the Fan-Out structure shown in Fig. 2. The conductive structure (330) spaced apart from the top and bottom inside the solid electrolyte (340) of Fig. 4 refers to a conductive material and is not limited to a specific structure or form specified in the present invention, but can be applied according to the implementer's utilization method, such as a conductive film layer or fiber. Fig. 5 is a drawing of a film among the conductive structures according to the embodiment.
[0052] The conductive structure (330) of Figures 4a and 4b above is located inside a sulfide-based solid electrolyte (340), and the sulfide-based solid electrolyte is characterized by being more brittle than an oxide-based one, so there are fewer limitations in combining specific shapes of the conductive structure (330).
[0053] The conductive structure (330) of Figures 4a and 4b is characterized by providing an effective solution for the electrical conductivity and ionic conductivity, and for the reduction in energy density that may occur by reducing the width of the solid electrolyte (340), based on the fixed conductive structure (330), regarding the delamination phenomenon that may occur between the electrode material and the solid electrolyte during the charging and discharging process of a conventional all-solid-state battery. Additionally, Figure 4c is a drawing showing a form in which the support structure surrounds not only the two sides of the electrolyte but also all four sides. As shown in Figure 4c, in the embodiment, the support structure may surround not only the two sides of the electrolyte but also all four sides.
[0054] Figures 6 and 7 are drawings showing the application structure of Fan-Out according to an embodiment.
[0055] In the embodiment, an electrode assembly structure utilizing a fan-out structure is proposed. In the embodiment, the basic structure is established by flipping one of two models—in which the EMC corresponding to the protective layer in a fan-out structure has been partially reduced—and combining them vertically. In the case of semiconductors, current flows horizontally (wiring insulator chip insulator wiring) as shown in FIG. 2, whereas in secondary batteries, the positive and negative plates must be connected vertically with an electrolyte in between to exchange ions. Utilizing this, an electrode is formed in a form where two wires connected to the solder ball shown in FIG. 3 are combined into one, and the two chips and EMC are combined vertically and replaced with a solid electrolyte and a supporting structure next to it. This structure can effectively control the disadvantages of the aforementioned all-solid-state battery. The detailed effects thereof are as follows.
[0056] The electrode assembly structure for a next-generation secondary battery according to the embodiment can compensate for the decrease in electrical conductivity and energy density caused by the delamination between the NCM and the solid electrolyte during the conventional charge-discharge process by arranging at least one of wiring, a conductive film layer, or a fiber, and can expect improved mechanical strength by partially preventing the delamination phenomenon. In addition, compared to the conventional solid electrolyte structure designed to be equal to the electrode plate width (Fan-In based on heterogeneous technology), structural stability can be secured by utilizing support structures on both sides, and the physicochemical resistance of the battery can be enhanced. Furthermore, in the embodiment, since a solid electrolyte with a narrower width can be used compared to the conventional solid electrolyte structure designed to be equal to the electrode plate width (Fan-In based on heterogeneous technology), the amount of expensive electrolyte used can be reduced. This enables the cost of the battery to be efficiently lowered.
[0057] In addition, in the embodiments, at least one of a conductive material in the form of an insulator, a conductive film layer, or a fiber is additionally disposed to prevent a decrease in electrical conductivity or energy density that may be caused by the reduction of the electrolyte volume.
[0058] Hereinafter, the application of a material that is compatible with and usable in the main parts through the electrode assembly structure according to the embodiment is described.
[0059] Electrode assembly support material
[0060] In the example, the support structure on both sides of the solid electrolyte for improving the physicochemical stability and structural stability of the battery is a support structure made of a polymer film, and the material can be manufactured by combining polyphenylene sulfide (PPS) and polyarylate (PAR) polymers into an interpenetrating network structure (IPN), as shown in FIG. 8.
[0061] An IPN (Interpenetrating Polymer Network) structure refers to a composite material formed by the mutual penetration of two or more polymer networks. Unlike an IPN structure, a Semi-IPN is a structure in which one of the two or more polymers forms a cross-linked structure while the other polymer exists within the cross-linked structure in a relatively free state. This Semi-IPN structure possesses greater flexibility and superior brittleness compared to an IPN. The IPN structure used in the examples can be formed through the following process. First, high-purity PAR powder and high-purity PPS powder are dissolved in their respective solvents (organic solvents containing NMP or DMF) to prepare a homogeneous solution. Next, a cross-linking agent and an initiator are added to the two solutions to form a homogeneous mixed solution. After preparing the solution formed in this way into a film, an IPN structure is formed through processes such as heat treatment or light irradiation at an appropriate temperature (approximately 300°C to 350°C).
[0062] Among the polymer materials used in the examples, polyphenylene sulfide (PPS) possesses excellent mechanical strength and structural stability when manufactured in the form of a film. It is also a material with excellent fire resistance and self-extinguishing properties. Furthermore, polyarylate (PAR), which forms an IPN structure similar to polyphenylene sulfide (PPS), is a polymer material that possesses mechanical strength and structural stability when manufactured in the form of a film, just like PPS, and exhibits high fire resistance and self-extinguishing properties. When using a mixed polymer material in which these materials are connected via an IPN structure, the different polymer materials are cross-linked and intertwined, resulting in superior mechanical strength compared to conventional films with general structures. When such a film is used as a support structure in the present invention, excellent structural stability can be expected. Using a composite material film connected by such a special structure as a support structure offers the following advantages.
[0063] First, both of the materials mentioned above (polyphenylene sulfide (PPS) and polyarylate (PAR)) can possess excellent mechanical and structural stability when manufactured in forms such as films. Furthermore, by forming a composite film using these materials through a special bonding structure like IPN, they can achieve even superior mechanical and chemical stability when used in a support structure. This resolves the stability issues of the electrode assembly caused by voids resulting from the use of a solid electrolyte with a narrower width than conventional methods, while simultaneously allowing for a more robust electrode assembly structure. Additionally, regarding the electrode structure of the present invention, which utilizes a solid electrolyte with a narrower width than the conventional concept of all-solid-state batteries that use highly fire-resistant solid electrolytes, the support structures located on both sides must also be made of highly fire-resistant materials. Therefore, it is expected that fire safety issues that may arise from using other polymer materials can be significantly reduced. Moreover, since the two polymer materials described above possess excellent mechanical strength and offer high price competitiveness compared to other polymer materials with superior fire resistance and self-extinguishing properties, a soft landing regarding the high cost of conventional all-solid-state batteries can be expected.
[0064] Electrode connecting material (binder)
[0065] In the examples, PTFE (polytetrafluoroethylene), a next-generation cathode binder, is included to improve the performance of the existing composite substrate presented in the problem. The PTFE used in the examples refers to a form of polyethylene in which all hydrogen atoms are substituted with fluorine. This material is chemically very stable and possesses excellent heat and corrosion resistance, making it widely used in various industries. Furthermore, using it as a cathode binder can improve the electrochemical characteristics and energy density of the battery. Additionally, as a hydrophobic material, PTFE can be easily utilized in dry electrode processes or all-solid-state batteries. When a certain amount of stress is applied to this PTFE at a specific temperature, a fiberization phenomenon occurs; by utilizing this property, a thin film can be formed without solvents and applied to the electrode by mixing the active material, conductive material, and binder and then extruding it.
[0066] Generally, wet processes are frequently applied for electrode manufacturing. However, the coating and drying stages within these wet processes account for approximately 20% of the manufacturing costs excluding raw material costs, and they have the disadvantage of consuming a large amount of electricity because the heat treatment process must be performed for 12 to 24 hours. Therefore, based on the performance comparison results shown in Figure 9, using PTFE allows for the application of a dry process instead of a wet one when manufacturing the cathode binder, thereby reducing time and costs and achieving better price competitiveness. When using such a cathode binder, the electrical connection between the conductive material and the active material within the electrode is strengthened, facilitating the movement of electrons. This reduces the internal resistance of the electrode and increases the power density of the battery. Furthermore, since it has superior bonding strength compared to the commonly used PVDF, it enhances the structural stability of the electrode, preventing performance degradation caused by the detachment of the active material or volume changes during cycling. Additionally, it maintains electrode uniformity, ensuring even distribution and adhesion of the active material. This improves the overall performance of the electrode and can maximize energy density. In addition, since manufacturing is possible in a dry process instead of the widely used wet process, the time and cost consumed compared to the existing process are reduced, allowing for superior price competitiveness in the manufacturing process of the battery itself compared to before.
[0067] The electrode assembly for a next-generation secondary battery and the method for manufacturing the same as described above
[0068] The decrease in electrical conductivity and energy density caused by delamination between the NCM and the solid electrolyte during the conventional charge / discharge process can be compensated for, and structural stability and physicochemical resistance of the battery can be improved by utilizing support structures on both sides compared to conventional electrodes. The support structures are made of materials with strong fire resistance and self-extinguishing properties, incorporating the advantages of fire-resistant solid electrolytes, and the electrode structure using a smaller amount of solid electrolyte than conventional solid electrolytes can resolve the cost issue that is a problem of conventional all-solid-state batteries.
[0069] In addition, through the embodiments, the electrical connection between the conductive material and the active material within the electrode can be strengthened to facilitate the movement of electrons. This allows for a reduction in the internal resistance of the electrode and an increase in the power density of the battery.
[0070] In addition, as shown in the examples, the bonding strength is superior compared to the commonly used PVDF, thereby increasing the structural stability of the electrode and preventing performance degradation caused by the detachment of the active material or volume changes during cycling.
[0071] In addition, the uniformity of the electrode is maintained through the examples, ensuring even distribution and adhesion of the active material. This improves the overall performance of the electrode and can maximize energy density.
[0072] In addition, through the examples, manufacturing in a dry process is possible as an alternative to the commonly used wet process, thereby reducing the time and cost consumed compared to the existing process and enabling superior price competitiveness in the manufacturing process of the battery itself.
[0073] The disclosed content is merely illustrative and can be modified and implemented in various ways by a person skilled in the art without departing from the gist of the claim in the patent claims; therefore, the scope of protection of the disclosed content is not limited to the specific embodiments described above.
Claims
Claim 1 A connecting material and an electrode assembly structure for manufacturing an all-solid-state battery, comprising: an adhesive material including a polytetrafluoroethylene (PTFE) binder interposed between a polymer film support layer and a conductive layer to bond the polymer film support layer and the conductive layer; an electrode assembly structure formed by including support structures on both sides of a solid electrolyte and covering the top and bottom with a positive plate and a negative plate; a solid electrolyte located between the positive and negative electrodes; and a conductive structure mounted between the electrode plates and the electrolyte in the assembly structure. The electrode assembly comprises a structure in which unit structures having a fan-out structure with a lower protective layer removed and support structures formed on both sides of the solid electrolyte are combined in an upside-down manner, and the electrode of the electrode assembly has a structure in which two wires spaced apart from each other in the unit structures are electrically connected to form a single electrode, the support structure has a width corresponding to the width difference between the upper and lower electrode plates and the solid electrolyte, the support structures on both sides of the solid electrolyte include a polymer film formed by combining polyphenylene sulfide (PPS) and polyarylate (PAR) polymers into an interpenetrating network (IPN) structure, the polymer film of the IPN structure is heat-treated at a temperature of 300°C to 350°C to improve mechanical strength and chemical stability, the conductive structure is positioned to mitigate the decrease in electrical conductivity due to the reduction in electrolyte volume, the support structure is formed to suppress detachment due to volume changes occurring during charging and discharging, the solid electrolyte is formed with a width reduced relative to the electrode plate while being supported by the support structure, and the conductive structure is inside the solid electrolyte An electrode assembly structure that is spaced apart and the support structure is formed to suppress interfacial detachment due to volume change occurring during charging and discharging. Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 delete Claim 6 delete Claim 7 In claim 1, the electrode assembly structure comprises a conductive structure located between the electrolyte and the anode plate to improve electrical conductivity and energy density. Claim 8 In claim 7, the conductive structure is an electrode assembly structure spaced apart above and below the solid electrolyte. Claim 9 In claim 7, the conductive structure comprises an electrode assembly structure including a conductive film layer or fiber for improving electrical conductivity and energy density. Claim 10 In claim 9, the conductive structure comprises: a conductive film layer or fiber containing at least one of copper, nickel, aluminum, and silver, a metallic material in the form of a metal fiber or foil; a carbon-based material comprising any one of graphite, carbon black, carbon fiber, carbon nanofiber, and carbon nanotube; a conductive polymer of a polyphenylene derivative or a polyaniline derivative; and an electrode assembly structure comprising a mixture of the metallic material, the carbon-based material and the conductive polymer. Claim 11 delete Claim 12 In claim 1, the electrode assembly structure wherein the solid electrolyte is a solid electrolyte made of a sulfide-based material. Claim 13 In claim 12, the solid electrolyte made of the sulfide-based material has an argyrodite-type crystal structure and comprises a compound represented by the following chemical formula Li6PS5X, wherein X is one or more elements selected from Group 17 of the periodic table, and the element comprises at least one of Cl, Br, and I, forming an electrode assembly structure.
Citation Information
Patent Citations
Lithium secondary batterh and manufacturing thereof
KR1020210105199A
All Solid secondary battery
KR1020240031908A
Long life thin film battery and method therefor
US6994933B1
